Uji Efektivitas Antibakteri Ekstrak Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Terhadap Pertumbuhan BakteriStaphylococcus epidermidis - FATTYA MURSYIDA; Husnarika febriani; rasyidah rasyidah (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2021)
Fragrant pandanus leaves (Pandanus amaryllifolius Roxb.) commonly used as additives in food has a compound content that includes flavonoid compounds, alkaloids, saponins, tannins, and polyphenols and dyes are suspected to contribute as antibacterial. In addition, the content contributes to other activities such as antidiabetic, chemical content in leaves that are suspected to be antibacterial are flavonoids. The purpose of this study is to find out if pandanus fragrant leaf extract (Pandanus amaryllifolius Roxb.) effectively inhibits the growth of staphylococcus epidermidis bacteria and know what concentration of fragrant pandan leaf extract (Pandanus amaryllifolius Roxb.) is effective in inhibiting the growth of staphylococcus epidermidis bacteria. The method used in this study was disc diffusion method with concentrations of 30%, 50%, 70%, 90% and 100% respectively.The results in this study pandan leaf extract fragrance (Pandanus amaryllifolius Roxb.) able to inhibit the growth of bacteria Staphylococcus epidermidis, with results obtained at a concentration of 30% obtained on average 2 mm, concentration 50% 2.3 mm, concentric 70% 9.6 mm, concentric 90% 10.6 mm and at 100% concentricity obtained the largest average of 14 mm is done each 3 repetitions. Effective concentration inhibits the growth of staphylococcus epidermidis bacteria at a concentration of 100%. Positive control used in this study is antibiotics (erythromycin) obtained an average tasteless zone of 30.3 mm in 3 repetitions while in negative control using sterile aquadest does not indicate the presence of a tasteless zone around the disc paper.